Peningkatan Kelancaran Membaca Kalimat Siswa Slow Learner Melalui Guided Reading Berbasis Kontekstual: Improving Sentence Reading Fluency of Slow-Learning Students Through Context-Based Guided Reading - Hasan Setiadi; Ishartiwi Ishartiwi (ITScience (Information Technology and Science), 2026)
Sentence reading fluency is a crucial skill that enables students to acquire information and comprehend texts. Two sixth-grade